2022
DOI: 10.38108/ouhcd.954519
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nursing Thesis Using Complementary Therapies and Supportive Care Applications During Drug Applications and Blood Collection

Abstract: Amaç: Bu çalışmada ilaç uygulamaları ve kan alma işlemi sırasında tamamlayıcı terapiler ve destekleyici bakım uygulamalarını kullanan hemşirelik tezlerinin incelenmesi amaçlanmıştır. Yöntem: Veriler nitel araştırma yöntemlerinden doküman incelemesi tekniği ile toplanmıştır. Türkiye Yükseköğretim Kurulu Ulusal Tez Merkezi web sitesinde yer alan tüm hemşirelik ana bilim dalları kontrol edilerek, 2010-2020 yılları arasında yayınlanmış 6855 tezin özeti incelenmiştir. Araştırma kriterlerine uygun 85 tez hazır… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Similar to this study, in a study conducted by Demir Alkin and Beydağ (2020), significant differences were found between the perceived stress during pregnancy and the number of pregnancies [22] . Various studies in the literature have also reported that the number of pregnancies and the gestational week affect stress levels [3,23,24] . Experiencing pregnancy for the first time, which is an important process in a woman's life, can lead to stress due to the woman facing an unknown situation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to this study, in a study conducted by Demir Alkin and Beydağ (2020), significant differences were found between the perceived stress during pregnancy and the number of pregnancies [22] . Various studies in the literature have also reported that the number of pregnancies and the gestational week affect stress levels [3,23,24] . Experiencing pregnancy for the first time, which is an important process in a woman's life, can lead to stress due to the woman facing an unknown situation.…”
Section: Discussionmentioning
confidence: 99%
“…It was developed by Yıldırım (2004) to measure perceived partner support. The scale is of a three-point Likert type (Suitable for me = 3, Partially suitable = 2, Not suitable for me = 1), and three items (10,20,24) on the scale are scored in reverse. The scale yields a minimum score of 27 and a maximum score of 81, with higher scores indicating greater perceived spousal support.…”
Section: Spousal Support Scale (Sss)mentioning
confidence: 99%
See 1 more Smart Citation